2010
DOI: 10.1590/s0066-782x2010005000004
|View full text |Cite
|
Sign up to set email alerts
|

Padrão de remodelação e função ventricular em ratos expostos à fumaça do cigarro

Abstract: Background: The relevance of the remodeling pattern in the model of rats exposed to cigarette smoke is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…In addition, the echocardiographic findings obtained in this study (SMs vs. the C) were in accordance with previous reports related to cardiac structural manifestations of smoking (increased wall thickness and/or cardiac mass) in animal models (42). …”
Section: Discussionsupporting
confidence: 93%
“…In addition, the echocardiographic findings obtained in this study (SMs vs. the C) were in accordance with previous reports related to cardiac structural manifestations of smoking (increased wall thickness and/or cardiac mass) in animal models (42). …”
Section: Discussionsupporting
confidence: 93%
“…Considering the consequences of the remodeling process, previous studies have shown that animals exposed to TS presented different remodeling patterns, including hypertrophy, dilation, hypokinesis and dysfunction. 3 , 21 , 26 - 29 The present data showed that TS changed the cardiac morphology, as evidenced by the higher left atrium area and myocytes hypertrophy. In addition, TS lowered the +dp/dt, a parameter of cardiac systolic function under controlled conditions.…”
Section: Discussionsupporting
confidence: 56%
“…The combined exposure group showed an joined effect of the two environmental risk factors on the most frequently studied lung abnormalities (airway wall thickening, end-terminal airspace dilation and inflammatory infiltrate), followed by the group exposed to inhaled cigarette smoke and nasal instillation of a suspension of particulate matter from fossil fuels, thereby enhancing the combined effect of both types of exposure. In an experimental model used to study cardiac alterations triggered by smoking, Azevedo et al 51 developed a controlled model of mice exposure to cigarette smoke for two months. At the end of the period, the exposed group showed higher incidences of concentric and eccentric myocardial hypertrophy shown at the echocardiography.…”
Section: Experimental Studiesmentioning
confidence: 99%